PENGARUH MODEL PEMBELAJARAN RESOLUSI KONFLIK BERBASIS CATUR PARAMITHA TERHADAP SIKAP SOSIAL DAN HASIL BELAJAR PENDIDIKAN AGAMA HINDU DAN BUDIPEKERTI SISWA KELAS VI GUGUS VI BATURITI - Gusti Ayu Agung Sri Wahyuni; I Made Sedana (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2023)
The aim of the study was to determine the effect of the chess paramitha-based conflict resolution learning model on social attitudes and learning outcomes of Hinduism for class VI Cluster VI Baturiti students. Data were analyzed using MANOVA with the help of SPSS 17.0 for windows. A total of 73 students were selected as samples by random sampling technique. The data collected is data on social attitudes and learning outcomes. The results showed that: first, there were differences in social attitudes between students who took the Catur Paramitha-based conflict resolution learning model and students who took conventional learning with an F value of 5.071 with a significance less than 0.05. second, there are differences in learning outcomes of Hinduism between students who take the Catur Paramitha-based conflict resolution learning model and students who take conventional learning with an F value of 10.829 with a significance less than 0.05. Third, there are simultaneous differences in social attitudes and learning outcomes of Hinduism between students who follow the Catur Paramitha-based conflict resolution learning model and students who take conventional learning in class VI SD Gugus VI Baturiti with an F value of 79.39